الجريمة الالكترونية في التشريع الجزائري - عديلة مراد -عبدلي ردوان (جامعة المسيلة, 2021)
يعرف العصر الحالي العديد من التطورات العلمية، ومن بينها التطور الحاصل الذي تشهده الثورة المعلوماتية و الالكترونية والانتشار الواسع للشبكة العنكبوتية، والتي ساهمت بشكل كبير في تطور العديد من مجالات الحياة. غير انه في المقابل أنتجت هذه الثورة نمط جديد من أنواع الجريمة وهي الجريمة الالكترونية والمعلوماتية، وهي جريمة تمس في صميمها قيما جوهرية تخص الأفراد والمؤسسات وحتى الدول فتسارعت العديد من الدول لإيجاد الحلول لها من خلال التشخيص العلمي الدقيق لمختلف العوامل الكامنة وراءها والتعرف على مختلف الاستراتيجيات والآليات التي تؤدي إلى الحد منها، ومن هنا يقترح الباحث مداخلة نتطرق فيها إلى استعراض جملة من المفاهيم المتعلقة بالمشكلة والمتمثلة في مفهوم الجريمة الالكترونية لدى مجموعة من العلماء. وتعريفها في التشريع الجزائري، وكذلك خصائص هذا النوع من الجرائم ومرتكبها، بالإضافة إلى مجالات استخدامها، وأخيرا أهم الآليات والسبل التي يمكن استغلالها من اجل التصدي لها. مما لا شك فيه أن الصعوبات التي تعترض سبل مكافحة الجريمة المعلوماتية متعددة، وكلها تنبع من كون هذه الجرائم تختلف جملة وتفصيلا عن الجرائم العادية، الأمر الذي بات يثير بعض التحديات القانونية والعملية أمام الأجهزة المعنية بمكافحتها، سواء أثناء إجراءات الاستدلال والتحقيق عبر البيئة الافتراضية لتعقب المجرمين وتقديمه للعدالة، أو خلال ملاحقة الجناة وكشف جرائمهم عبر الحدود. لذلك تثور العديد من المشكلات والتي تقف عائقا أمام مكافحة الجريمة المعلوماتية، منها ما يتعلق بالكشف عن الجريمة المعلوماتية، كما قد يبرز للوجود صعوبات متعلقة بالتعاون القضائي الدولي وتحديد قواعد الاختصاص. الكلمات المفتاحية: الجريمة الالكترونية، أنظمة المعالجة الآلية للمعطيات. صعوبات مواجهة الجريمة الالكترونية – اكتشاف واثبات الجريمة الالكترونية – التعاون الدولي في مجال الجريمة الالكترونية. Abstract : The current era is known for many scientific developments . one of wich is development in the information and electronic revolution and high prevalence of the web that contributed greatly to the progress of many areas of life. On the other hand , this revolution produced a new type of crime, namely electronic or informatoin crime. The latter, at its core, affects the fundamental values of individuals, institutions and even countries. Consequently, many countries have accelerated to find solutions through accurate scientific diagnosis of the various factors behind it, and identify the different strategies and mechanimsms to reduse it. This research paper attempts to describe cybercrime and provide definitions and related concepys set by scholars, and its definition in the Algrian legislation. The paper also illustrates of this crime, its perpetrators, areas of use and the most important mechanisms and ways to confront it. Undoubtedly, there are many problems hampering the process of fighting cybercrime . Thay are all due to the fact that these crimes are totally diffrent from ordinary crimes. This raises some legal and operational challenges for the systems in charge of its fight. The challenges may intervene at the stage of gathering evidence and investigating through the virtual space to detect criminals and prosecute them, or at stage of tracking criminals and detecting their crossborder crimes. Thus , many problems arise in the way of fighting cybercrimes, some of them are related to the detection of the crime and the identification of criminals and other are related to proving the cybercrime. Other problems may arise in relation to difficulties in the international judicial cooperation and the determination of jurisdictional rules. Key words : Cybercrime, Automatic data processing systems. – difficulties in fighting cybercrimes – detection and confirmation of cybercrimes – international judicail cooperation in matters of cybercriminality.
Keywords: الجريمة الالكترونية، أنظمة المعالجة الآلية للمعطيات. صعوبات مواجهة الجريمة الالكترونية – اكتشاف واثبات الجريمة الالكترونية – التعاون الدولي في مجال الجريمة الالكترونية.